http://zmj.zsmu.edu.ua/article/view/18936/16626 - N. P. Shastun (Zaporožskij Medicinskij Žurnal)
The problem of choose of the safe anticonvulsant for the treatment of epilepsy is quite relevant. When choosing a drug, the physician should strive to balance the frequency of attacks and the severity of side effects in each individual patient. Rational antiepileptic therapy should improve the quality of life of the patient and his social adaptation.